Polarization-insensitive Tunable Silicon Photonic Optical Filters for Data Center Transceivers - Alnairat, Saif; Schmauß, Bernhard; Wohlfeil, Benjamin; Djordjevic, Stevan S.; Elbers, Jörg Peter (IEEE International Conference on Group IV Photonics GFP, 2024)
We demonstrate a polarization-independent tunable silicon photonic integrated optical filter for high-speed optical transceivers. The device utilizes Polarization Splitter-Rotators (PSRs) and Vernier Microring Resonators (MRRs). The filter is configured and thermally tuned continuously across the C-band, within a feasible maximum temperature change of (70-80) K.
CRIS-Team Scopus Importer:2024-07-05
Keywords: integrated heaters; optical filters; ring resonators; silicon photonics; transceiver